Assessment of Global Health Education: The Role of Multiple-Choice Questions - Douthit, Nathan T.; Norcini, John; Mazuz, Keren; Alkan, Michael; Feuerstein, Marie-Therese; Clarfield, A. Mark; Dwolatzky, Tzvi; Solomonov, Evgeny; Waksman, Igor; Biswas, Seema (Frontiers in Public Health, 2021)
Abstract Introduction: The standardization of global health education and assessment remains a significant issue among global health educators. This paper explores the role of multiple choice questions (MCQs) in global health education: whether MCQs are appropriate in written assessment of what may be perceived to be a broad curriculum packed with fewer facts than biomedical science curricula; what form the MCQs might take; what we want to test; how to select the most appropriate question format; the challenge of quality item-writing; and, which aspects of the curriculum MCQs may be used to assess. Materials and Methods: The Medical School for International Health (MSIH) global health curriculum was blue-printed by content experts and course teachers. A 30-question, 1-hour examination was produced after exhaustive item writing and revision by teachers of the course. Reliability, difficulty index and discrimination were calculated and examination results were analyzed using SPSS software. Results: Twenty-nine students sat the one-hour examination. All students passed (scores above 67% - in accordance with university criteria). Twenty-three (77%) questions were found to be easy, 4 (14%) of moderate difficulty, and 3 (9%) difficult (using examinations department difficulty index calculations). Eight questions (27%) were considered discriminatory and 20 (67%) were non-discriminatory according to examinations department calculations and criteria. The reliability score was 0.27. Discussion: Our experience shows that there may be a role for single-best-option (SBO) MCQ assessment in global health education. MCQs may be written that cover the majority of the curriculum. Aspects of the curriculum may be better addressed by non-SBO format MCQs. MCQ assessment should complement other forms of assessment that might better assess skills, attitude and behavior. Preparation of effective MCQs is an exhaustive process, but high quality MCQs in global health may serve as an important driver of learning.